2023
DOI: 10.5620/eaht.2023006
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary characterization and probabilistic risk assessment of microplastics and potentially toxic elements (PTEs) in garri (cassava flake), a common staple food consumed in West Africa

Abstract: Garri from cassava is one of the most consumed foods in West Africa, hence this research was conducted to examine microplastics (MPs) and potentially toxic elements (PTEs) in garri from Nigeria (West Africa) and Japan. This is the first investigation on MPs in garri samples that has been reported in the literature. The study analyzed both packaged and unpackaged vended garri samples using microscopic/spectroscopic and X-ray fluorescence techniques for MPs and PTEs respectively. Microplastic particles in the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 94 publications
1
4
0
Order By: Relevance
“…The results in this study are similar to that in research conducted in Bushehr city, Iran, where fibers were abundant, constituting 75% of the MPs in street dust samples [50]. Other types of MPs were coming to the street dust from the discharge of plastic items [29].…”
Section: Source Appraisal By Principal Component Analysis (Pca) For M...supporting
confidence: 88%
See 4 more Smart Citations
“…The results in this study are similar to that in research conducted in Bushehr city, Iran, where fibers were abundant, constituting 75% of the MPs in street dust samples [50]. Other types of MPs were coming to the street dust from the discharge of plastic items [29].…”
Section: Source Appraisal By Principal Component Analysis (Pca) For M...supporting
confidence: 88%
“…Concerning the line, the picture displayed a form that resembled a strand or a lengthy and narrow impression or stroke, which is greater in length than in width. On the other hand, the film appeared like a slim sheet [29]. Multiple studies have reported the presence of these shapes in street dust in many world cities [41][42][43].…”
Section: Distribution Of Particles and Mps In Samplesmentioning
confidence: 98%
See 3 more Smart Citations